The Transformative Methodology: Expository Study of Teaching English as the Second Language Acquisition - Jacob Tshepang Moloi; Emmanuel Tobi Adegoriolu (Research in Social Sciences and Technology- OpenED Network, 2021)
The significance of language as a science in the educational sector has continued to play a critical role in terms of teaching and learning. However, due to inequalities exposed severely by the Covid-19 pandemic, the teaching of English as the second language acquisition to foreign speakers; is adversely affected. Therefore, the use of transformative methodology as the teaching strategy is explored to determine the most suitable methodology of teaching during the Covid-19 pandemic. The study utilizes Participatory Action Research as the approach to explore the efficacy of transformative methodology; this approach is embedded in the paradigmatic principles of constructivism as the lens of qualitative methodology. Besides, the data is analysed using Critical Discourse Analysis post the generation of it using observations and semi-structured interviews (free attitudinal interviews). The paper demonstrates the prospects of using transformative methodology as the appropriate use of pedagogical strategy for English as the second language acquisition, it also suggests efficient but costly measures required to be implemented by the universities for the use of the transformative methodology.